Kosmologi Islam Kasultanan Ngayogyakarta Hadiningrat - Lailatuzz Zuhriyah (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2013)
This article scrutinizes the concept of cosmology held by the Kasultanan Ngayogyakarta Hadiningrat. The writer observes that the process of Islamization in Java island has, more or less, influenced the mindset of Javanese people, including the people of Kasultanan Ngayogyakarta Hadiningrat. Once Islamized, the Sultanate has adapted Islamic teachings and made them a part of its cultural mindset. In this stage, the acculturation has been done successfully. Such acculturation has subsequently influenced their view on cosmology, which is different from—and does not reflect—Hinduism’s and Buddhism’s cosmology. The use of the title Senopati ing Alaga Sayidin Panatagama Khalîfatullah by Yogyakarta sultans clearly indicates that they respect the old concept. Since the advent of Islam, Javanese culture, including the culture of the Sultanate of Yogyakarta, has been subsequently Islamized.